Using motion-based estimated action of the diver to characterize diving board dynamics: a pilot study - Demestre, L.; Audoux, Y.; Grange, S.; Bideau, N.; Nicolas, G.; Pontonnier, C.; Dumont, G. (Computer Methods in Biomechanics and Biomedical Engineering, 2021)
The diving board model parameters were obtained after a calculation time of 25 min. Experimental and numerical vertical displacements at the free edge were compared. The maximal discrepancy between experimental and numerical displacements is observed after 5.3 s, when the diving board reaches its maximum deflection. This discrepancy is 2.9 cm, which is 11% of the maximal experimental deflection. The mean values of M, P and C are respectively 4.8%, 1.3% and 5.0%. One can conclude that the method enables to obtain a model behaviour close to the experimental one.The diving board model is going to be improved to take into account space-variable IF&M. The application point of the IF&M should take into account the centre of pressure position under the subject`s feet. The characterization method is also going to be improved to take into account several trials at the same time. The characterization method described is a new tool to obtain a suitable model of a diving board studied experimentally. This method is appropriate for coupled structure dynamics study of the diving board and biomechanical analysis of the diver. In the future, such a model may be a primary importance to evaluate in depth time synchronization between the diver and the diving board.